KONSEP WELFARE STATE PADA KEBIJAKAN UMAR BIN ABDIL AZIZ SEBAGAI KHALIFAH BANI UMAYYAH - Kusumastuti, Annisa Silvi; Ghozali, Mohammad (ASAS, 2020)
Caliph Umar bin Abdul Aziz succeeded in implementing the concept of welfare state, namely prosperous state. Umar has a new policy to change the lives of people. One of the evidence is that there is no find one who can accept zakat because the whole community has been sufficient. Therefore, this research aims to know how Umar's strategy is to create prosperity for the community. The study used qualitative methods using the literature review taken from several books, journals, and several relevant reading sources. From the results of the research is known that Umar's policy strategy is by distributing a wealth of government officials with a fair and flat, but Umar also spent the Harat in Baitul Maal to pay the debt of society.  Even when he was appointed Caliph, he gathered his people and announced and handed over all his unnatural possessions and family to Baitul Maal. In the event that Umar banned the sale of land Kharaj because it could be the main source of State acceptance. In the time of his glory, Caliph Umar received a source of acceptance of the state from Zakat, Jizyah, Kharaj, ' Usyr, and Ghanimah and Fa'i.Keywords: welfare state, policy, caliph Umar bin Abdul Aziz